The similarities in efficiency of universities and universities of applied sciences in Lower Saxony - Britta Stöver; Philipp Sibbertsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
Due to the advancing economisation and the associated discussion on the distribution of public budgets and tax revenues, the efficiency of higher education institutions is increasingly coming into focus. Since the 2000s, more and more studies on the efficiency of German universities have been published. While the research focus and the applied methods differ between these studies, the majority have in common that they exclude universities of applied sciences from the data set. The aim of this paper was to show differences and commonalities in efficiency between universities of applied sciences and universities in Lower Saxony. Based on an exclusive data set, the efficiency values were estimated using Data Envelopment Analysis and Stochastic Frontier Analysis including the analysis of efficiency changes, influencing factors and ranking differences between both methods. The central findings are that (1) there existed no significant differences in efficiency between universities and universities of applied sciences, (2) that an alignment process took place between 2010 and 2017 leading to a higher similarity in efficiency and (3) that the ranking and the level of efficiency depends very much on the choice of method stressing the necessity to settle on one method when using it for monitoring purposes.
Keywords: C14; C23; C61; D61; I22; I23; 330; Data Envelopment Analysis (DEA); Stochastic Frontier Analysis (SFA); efficiency; university (of applied sciences); Lower Saxony (Germany)